Single Sampling Plan for Variable Indexed by AQL and AOQL with Known Coefficient of Variation - Singh, JR; Sanvalia, A (International Journal of Computer Sciences and Engineering, 2025)
In this paper we have studies the effect of coefficient of variation (CV) on single sampling plan for variables indexed by acceptable quality level (AQL) and average outgoing quality limit (AOQL)based on the assumption of normality and independence are affected when the characteristic of an item possesses a normal distribution. Procedures and tables are given for the selection of single sampling plans for variables for given AQL and AOQL, whenever rejected lots are 100% inspected for replacement of nonconforming units. The operating characteristic (OC) function is described for different values of coefficient of variation. It is clear that the value of OC function with known CV shows higher values for the lot of bad quality. The values of n and k are also calculated with known coefficient of variation.